Determination of Technological Properties and CRISPR Profiles of Streptococcus thermophilus Isolates Obtained from Local Yogurt Samples - Coban, Hatice Sevgi; Olgun, Dicle; Temur, Inci; Durak, Muhammed Zeki (MDPI, 2024)
The aim of this study was to obtain data on Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) profiles of Streptococcus thermophilus (S. thermophilus) isolates resulting from acquired immune memory in addition to their technological starter properties for the selection of potential starter cultures from local yogurt samples. A total of 24 S. thermophilus isolates were collected from six local yogurt samples including Afyon/Dinar, U & scedil;ak, Konya/Karap & imath;nar, and Tokat provinces of T & uuml;rkiye. Strain-specific CRISPR I-II-III and IV primers were used to determine the CRISPR profiles of the isolates. The isolates commonly had CRISPR II and IV profiles, while only one isolate had a CRISPR III profile. Polymerase chain reaction (PCR)-based and culture-based analyses were also carried out to obtain data on the technological properties of the isolates. The PCR analyses were performed for the prtS gene for protease activity, the ureC gene for urease enzyme, the gdh gene for glutamate dehydrogenase, the cox gene for competence frequency, the csp gene involved in heat-shock stress resistance of the isolates with specific primers. Culture-based analyses including antimicrobial activity and acid-production ability of the isolates were completed, and proteolytic and lipolytic properties were also screened. Native spacer sequences resulting from acquired immune memory were obtained for CRISPR IV profiles of yogurt samples from the Konya-Karap & imath;nar and Tokat provinces and CRISPR III profiles of yogurt samples from the U & scedil;ak province. In conclusion, our study results suggest that it is possible to select the isolates with the desired level of technological characteristics, prioritizing the ones with the most diverse CRISPR profiles and with native spacers for potential industrial application as starter cultures. We believe that this study provides data for further biological studies on the impact of centuries of human domestication on evolutionary adaptations and how these microorganisms manage survival and symbiosis.
Keywords: Streptococcus thermophilus; yogurt; CRISPR; technologically important proteins; LACTIC-ACID BACTERIA; IMMUNE-SYSTEM; COLD SHOCK; IDENTIFICATION; GENES; CLASSIFICATION; PROKARYOTES; BULGARICUS; RESISTANCE; DIVERSITY; Microbiology